#WeToo: Feminist Therapist Self-Disclosure of Sexual Violence Survivorship in a #MeToo Era. Issue 1 (2nd January 2022) - Bennett, Elizabeth A.; Koelsch, Lori E.; Kuppers, Susannah R.; King Ash, Sheree
Abstract: In this article, we present a review of the #MeToo movement alongside therapeutic, feminist self-disclosure by situating feminist self-disclosure in dialogue with and in response to the current #MeToo era of mainstream self-disclosures regarding sexual violence. We consider issues of transference and countertransference when therapists who are survivors work with survivors of sexual violence in therapy, and we employ the categories of the Feminist Self-Disclosure Scale as a guiding framework for the possible benefits of therapist self-disclosure in relation to #MeToo. We discuss different and provocative ways in which feminist clinicians conceptualize self-disclosure as compared to dominant therapeutic models, while also exploring potential ethical questions. Importantly, we present eight suggested practices that have developed through our engagement with clinical work. These suggested practices range from exploring the therapist's use of office décor to utilizing supervision as a modality for discussing survivorship; within each suggested practice, we provide a clinical example to illuminate the practice and provide a concrete way in which the reader might employ the practice. We also provide ideas for therapists who are not survivors themselves to convey allyship.